Pengaruh Due Professional Care terhadap Kualitas Audit pada Inspektorat Daerah Provinsi Nusa Tenggara Timur - Tiffany N. P. Gah; Arnolus Lesik (STIE Kertanegara Malang, 2023)
The research aims to examine the effect of due professional care on audit quality of auditors at the NTT Provincial Inspectorate. Data collection was carried out by survey using a questionnaire. The independent variable (x) is due professional care and the dependent variable (y) is audit quality. Testing begins with validity and reliability tests, followed by classic assumption tests in the form of normality and linearity tests. After that, a simple linear regression, correlation coefficient (R), coefficient of determination (R2) and hypothesis testing were carried out. Testing is done with the help of SPSS. Testing the hypothesis states that due professional care has an significance effect on audit quality. The results also show that due professional care has a positive effect on audit quality, which means that the due professional care relationship is in the same direction as audit quality